Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the given system of equations:
[tex]\[ \begin{array}{c} 2x + 7y = -1 \\ 4x - 3y = -19 \end{array} \][/tex]
We can use the method of elimination to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex].
Step 1: Align the equations and prepare them for elimination.
[tex]\[ \begin{array}{rl} (1) & 2x + 7y = -1 \\ (2) & 4x - 3y = -19 \end{array} \][/tex]
Step 2: Eliminate one variable.
We will eliminate [tex]\(x\)[/tex] by making the coefficients of [tex]\(x\)[/tex] in both equations equal. To do this, we can multiply equation [tex]\((1)\)[/tex] by 2:
[tex]\[ 4x + 14y = -2 \quad \text{(which is our new equation (3))} \][/tex]
Now, we have:
[tex]\[ \begin{array}{rl} (3) & 4x + 14y = -2 \\ (2) & 4x - 3y = -19 \end{array} \][/tex]
Step 3: Subtract equation (2) from equation (3) to eliminate [tex]\(x\)[/tex]:
[tex]\[ (4x + 14y) - (4x - 3y) = -2 - (-19) \][/tex]
[tex]\[ 4x + 14y - 4x + 3y = -2 + 19 \][/tex]
[tex]\[ 17y = 17 \][/tex]
[tex]\[ y = 1 \][/tex]
Step 4: Substitute [tex]\(y = 1\)[/tex] back into one of the original equations to find [tex]\(x\)[/tex].
We substitute [tex]\(y = 1\)[/tex] into equation (1):
[tex]\[ 2x + 7(1) = -1 \][/tex]
[tex]\[ 2x + 7 = -1 \][/tex]
[tex]\[ 2x = -1 - 7 \][/tex]
[tex]\[ 2x = -8 \][/tex]
[tex]\[ x = -4 \][/tex]
Conclusion:
The solution to the system of equations is [tex]\((-4, 1)\)[/tex].
[tex]\[ \begin{array}{c} 2x + 7y = -1 \\ 4x - 3y = -19 \end{array} \][/tex]
We can use the method of elimination to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex].
Step 1: Align the equations and prepare them for elimination.
[tex]\[ \begin{array}{rl} (1) & 2x + 7y = -1 \\ (2) & 4x - 3y = -19 \end{array} \][/tex]
Step 2: Eliminate one variable.
We will eliminate [tex]\(x\)[/tex] by making the coefficients of [tex]\(x\)[/tex] in both equations equal. To do this, we can multiply equation [tex]\((1)\)[/tex] by 2:
[tex]\[ 4x + 14y = -2 \quad \text{(which is our new equation (3))} \][/tex]
Now, we have:
[tex]\[ \begin{array}{rl} (3) & 4x + 14y = -2 \\ (2) & 4x - 3y = -19 \end{array} \][/tex]
Step 3: Subtract equation (2) from equation (3) to eliminate [tex]\(x\)[/tex]:
[tex]\[ (4x + 14y) - (4x - 3y) = -2 - (-19) \][/tex]
[tex]\[ 4x + 14y - 4x + 3y = -2 + 19 \][/tex]
[tex]\[ 17y = 17 \][/tex]
[tex]\[ y = 1 \][/tex]
Step 4: Substitute [tex]\(y = 1\)[/tex] back into one of the original equations to find [tex]\(x\)[/tex].
We substitute [tex]\(y = 1\)[/tex] into equation (1):
[tex]\[ 2x + 7(1) = -1 \][/tex]
[tex]\[ 2x + 7 = -1 \][/tex]
[tex]\[ 2x = -1 - 7 \][/tex]
[tex]\[ 2x = -8 \][/tex]
[tex]\[ x = -4 \][/tex]
Conclusion:
The solution to the system of equations is [tex]\((-4, 1)\)[/tex].
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.